Towards more inclusive smart cities: Reconciling the divergent realities of data and discourse at the margins. Issue 9 (9th June 2020) - Lee, Jane Yeonjae; Woods, Orlando; Kong, Lily
Abstract: In this article, we survey a growing body of literature within geography and other intersecting fields that trains attention on what inclusive smart cities are, or what they could be. In doing so, we build on debates around smart citizens, smart public participation, and grassroots and bottom‐up smart cities that are concerned with making smart cities more inclusive. The growing critical scholarship on such discourses, however, alerts us to the knowledge politics that are involved in, and the urban inequalities that are deeply rooted within, the urban. Technological interventions contribute to these politics and inequalities in various ways. Accordingly, we discuss limitations of the current discourses around inclusive smart cities and suggest a need for a nuanced definition of 'inclusiveness'. We also discuss the necessity to further engage with critical data studies in order to 'know' what we are critiquing.